Needs Analysis for Developing Project-Based Learning Outcomes Assessment Models in Electricity topic at the Center of Excellence Vocational High School - Soeprijanto, Soeprijanto; Prohantoro, Rudy; Pratama, Rian; Ariefin, Dayu Adestamy (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2022)
This study aims to analyze the needs of the project-based learning outcomes assessment model at the Center for Excellence in Vocational High Schools. The first step in the research is the development of Project-Based Learning Assessment Models. Electricity was chosen because it is one of the intersecting materials in the departments at Vocational High Schools. The survey method was chosen to collect information on the needs of the assessment model. The survey data were analyzed using descriptive statistics. The mode of the survey data was used to draw the required model conclusions.The number of respondents who filled out the questionnaire was from 10 SMK-PK in DKI Jakarta, West Java, Banten, and Lampung who applied Project-Based Learning in Practical Teaching. From the respondents' answers, it can be concluded that. Most schools require specific Guidelines for the Assessment of Project-based Learning yet to be made available. Most teachers require industry involvement in the creation of Practice-based Learning assignments. A large number of teachers need an assessment of the quality of assignments. Assessment of the Project-based Learning Process tends to be carried out at the implementation stage, while in the planning and reporting stages, it is carried out by a few teachers. The assessment tends to be carried out against groups with aspects assessed as competence and student performance. The assessment techniques carried out include written tests, observations, and portfolios. Standard sample documents required include Instrument Indicators and Rubrics.